Exploring the Dependency between Energy Access and other Sustainable Development Goals: Global Evidence - Sadath, Anver C.; Acharya, Rajesh H. (International Journal of Energy Economics and Policy, 2024)
This paper examines the interlinkage between energy access and other Sustainable Development Goals (SDGs) in the global context. For this purpose, we have calculated the indices for all 17 SDGs and use correlation and path analysis under structural equation modelling framework. Empirical results confirm that SDG 7 has positive and significant correlation with goal 4 and goal 12 indicating that ensuring access to modern energy resources enables women and girls to spend more time on education and gainful employment than gathering fuel. Further, energy access fosters sustainable production and consumption pattern and also promotes food security and promoting sustainable agriculture.